Fostering Social Caring Through Multicultural-Based Language Learning - Adityas, M Tolkhah (Ahmad Dahlan Journal of English Studies, 2017)
Social caring can be interpreted as affection and attention to other people which can later be manifested in an appreciating, accepting, and helping behavior. The behavior is not automatically possessed by each individual. Instead, it should be learnt, understood, internalized, and implemented in daily life. This article aims at discussing the strategies to enhance students social caring through multicultural awareness in language learning. Social caring serves as character values which appreciates diversity. It needs to be internalized from the very early age so that each individual understands how to deal with diversity. One of the alternatives in supporting the implementation of social care character is through multicultural-based learning activities. Hopefully, this type of learning leads students to appreciate diversity. Â Keywords: character, social caring,Â  multicultural-based activities